The TLR4 adaptor TRAM controls the phagocytosis of Gram-negative bacteria by interacting with the Rab11-family interacting protein 2 - Skjesol, Astrid; Yurchenko, Mariia; Bösl, Korbinian; Gravastrand, Caroline; Nilsen, Kaja Elisabeth; Grøvdal, Lene Melsæther; Agliano, Federica; Patane, Francesco; Lentini, Germana; Kim, Hera; Teti, Giuseppe; Kumar Sharma, Aditya; et al. (PLoS pathogens, 2019)
Phagocytosis is a complex process that eliminates microbes and is performed by specialised cells such as macrophages. Toll-like receptor 4 (TLR4) is expressed on the surface of macrophages and recognizes Gram-negative bacteria. Moreover, TLR4 has been suggested to play a role in the phagocytosis of Gram-negative bacteria, but the mechanisms remain unclear. Here we have used primary human macrophages and engineered THP-1 monocytes to show that the TLR4 sorting adapter, TRAM, is instrumental for phagocytosis of Escherichia coli as well as Staphylococcus aureus. We find that TRAM forms a complex with Rab11 family interacting protein 2 (FIP2) that is recruited to the phagocytic cups of E. coli. This promotes activation of the actin-regulatory GTPases Rac1 and Cdc42. Our results show that FIP2 guided TRAM recruitment orchestrates actin remodelling and IRF3 activation, two events that are both required for phagocytosis of Gram-negative bacteria.